(untitled) (Research, Society and Development, 2025)
The urban expansion and the presence of green areas within cities have favored the interaction between humans and wild animals, making it essential to understand these encounters to ensure a balanced coexistence. This study investigated the presence of wildlife in urban areas of Maringá, Paraná, and the population’s perception of these animals. Questionnaires were applied to residents living near Parque do Ingá and Bosque II in Maringá-PR, along with data collection from organizations responsible for animal rescues, such as the Fire Department, the Instituto Água e Terra (IAT), and the Centro de Atendimento à Fauna Silvestre (CAFS) in the municipality. The research analyzed the main species observed, the attitudes of residents toward these encounters, and their level of knowledge regarding the ecological importance of local wildlife. The results indicated that many inhabitants are unaware of the ecological role of these species, and while they are accustomed to the presence of these animals, some residents still express fear or concern. Additionally, an increase in the number of wildlife rescues near the studied green areas was identified, reinforcing the need for educational initiatives and management strategies to minimize impacts and promote biodiversity conservation. The study highlights the importance of environmental education as a fundamental tool to raise awareness among the population and foster practices that encourage the coexistence between humans and wildlife in urban environments.